2015
DOI: 10.1155/2015/827380
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Proper Use of Polygoni Multiflori Radix, Cynanchi Wilfordii Radix, and Cynanchi Auriculati Radix in Korea: A Descriptive Review

Abstract: Polygoni Multiflori Radix (PMR), Cynanchi Wilfordii Radix (CWR), and Cynanchi Auriculati Radix (CAR) are very popular herbal medicines in Traditional Korean Medicine, Traditional Chinese Medicine, and Kampo Medicine. However, the plant origins, efficacies, and traditional uses of these herbal medicines differ. In Korea, PMR is called Ha Su O (He Shou Wu in China), and CWR is called Baek Ha Su O or Baek Su O (Bai Shou Wu in China). Baek Su O refers to CWR in Korea and CAR in China. CAR has not been used as a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In addition, as approximately 30% of the CWR used in Korea are Chinese products, 9) our present findings revealed that information about the market from which was purchased cannot be used to predict its original plant species.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, as approximately 30% of the CWR used in Korea are Chinese products, 9) our present findings revealed that information about the market from which was purchased cannot be used to predict its original plant species.…”
Section: Discussionmentioning
confidence: 73%
“…8) In addition to this problem, CWR is also sometimes misused as PMR because of the similarity in their Korean names of "Baek Ha Su O" and "Ha Su O," respectively. 9) Thus, the misuse of PMR, CWR, and CAR is a major concern in Korea.…”
mentioning
confidence: 99%
“…Polygonum mulitflorum Thunb (PMT) is mostly found in China, Korea and Japan, belonging to Polygonaceae family [ 245 ]. Radix Polygoni multiflori (root tubers of PMT) is mostly used in treating many kinds of diseases, such as rubella, scrofula, waist and knee pain, paralysis, vaginal discharge, hypercholesterolemia (liver and kidney), malaria, and various other diseases, possessing neuro-protective, antioxidation, immunomodulation, anti-hyperlipidemia, anticancer, heap-toprotection, anti-inflammation, and anti-CoV functions [ 86 , 87 , 246 ]. The potent bioactive compounds present in PMT which are responsible for the therapeutic effects against various diseases are listed in Table 1 [ 84 , 85 , 88 , 247 ].…”
Section: Known Medicinal Plants Acting On Ace-2 Receptormentioning
confidence: 99%
“…Cynanchi Auriculati Radix (CAR) is the root of Cynanchum auriculatum Royle ex Wight, and is also known as Baishouwu in China. CAR has valuable pharmacological properties, including antioxidant, immunomodulatory, antitumor, antihyperlipidemic, hair growth promotion and antidepressant activities (Lee & Lee, ). Its activities can be attributed to various compounds, such as cynauricuosides A, B and C, β ‐sitosterol, wilfosides C1N, C2N and C3N, penupogenin, vitamins and amino acids (Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…CAR is a popular traditional Chinese medicine, but is not used as a medicine in Korea. It is listed as a toxic material in the Poisonous Plant Database of the Food and Drug Administration in the USA (Lee & Lee, ; Li & Li, ). PMR and CAR differ in their plant origins, component compounds, pharmacological effects and toxicities.…”
Section: Introductionmentioning
confidence: 99%